Individualised Nursing Care Improves Symptom Control and Nutritional Tolerance in Women with Stage III Ovarian Cancer Undergoing Chemotherapy - Wahyu Wahyu; Machmudah Machmudah; Sri Rejeki (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Ovarian cancer is a leading cause of cancer related mortality among women and is frequently diagnosed at an advanced stage. Management of stage III disease typically requires multimodal treatment, including surgery and chemotherapy, both of which contribute to a substantial symptom burden and increased supportive care needs. As a result, comprehensive nursing care becomes essential to address the complex physical and psychosocial challenges experienced during active treatment. This case report aimed to describe the implementation of the nursing process in two women with stage III ovarian cancer undergoing active treatment in a referral hospital in Central Sulawesi, Indonesia. Data were collected through semi structured interviews, direct clinical observation, and documentation review using the Indonesian Nursing Diagnosis Standards framework. Both patients presented with nutritional deficits and nausea as primary nursing diagnoses. Additional problems identified in the first patient included acute pain, sleep disturbance, activity intolerance, and ineffective peripheral perfusion, whereas the second patient experienced a risk of infection related to colostomy and disturbed body image. Nursing interventions focused on symptom management, nutritional support, pain control, infection prevention, and psychosocial care. Evaluation demonstrated improvements in symptom control, increased tolerance to nutritional intake, and the absence of infection throughout hospitalization. In conclusion, individualized and holistic nursing care plays a critical role in enhancing clinical outcomes and patient comfort during active treatment for advanced ovarian cancer.Keywords: chemotherapy; nutritional deficit; nursing process; ovarian cancer; supportive care; symptom management